2016
DOI: 10.1111/bjd.14811
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatments for scalp psoriasis: summary of a Cochrane Systematic Review

Abstract: People with chronic plaque psoriasis often have lesions on the scalp that are difficult to treat. This report is a summary of a Cochrane review on the efficacy and safety of topical treatments for scalp psoriasis. For quality-of-evidence assessment, we used the Grading of Recommendations Assessment, Development and Evaluation Working Group approach. Only randomized controlled trials (RCTs) were eligible for inclusion. We searched the Cochrane Skin Group Specialised Register, CENTRAL, MEDLINE, Embase and LILACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…Indeed, a Cochrane systematic review on topical treatments for psoriasis concluded that most findings were limited to short-term treatments (<6 months) and that long-term assessments (6-12 months) are needed. 8 The concept and proposals regarding the use of topical therapy in the long-term management of psoriasis have evolved over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a Cochrane systematic review on topical treatments for psoriasis concluded that most findings were limited to short-term treatments (<6 months) and that long-term assessments (6-12 months) are needed. 8 The concept and proposals regarding the use of topical therapy in the long-term management of psoriasis have evolved over time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a Cochrane systematic review on topical treatments for psoriasis concluded that most findings were limited to short-term treatments (<6 months) and that long-term assessments (6–12 months) are needed. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Esta paciente nos permite recordar algunos conceptos sobre los cambios pilosebáceos en la psoriasis, especialmente la atrofia sebácea. El compromiso del cuero cabelludo ocurre en el 50-78% de los pacientes con psoriasis; la alopecia es frecuente, aunque es reversible con el tratamiento adecuado y temprano (1)(2)(3) . En el 7-12% de los casos se ha asociado con alopecia cicatricial, en pacientes con años o décadas de evolución de su enfermedad (4,5) .…”
Section: Diagnóstico Psoriasis Del Cuero Cabelludounclassified
“…2 The medications currently used to treat scalp psoriasis are topical corticosteroids, topical vitamin D analogues and tar shampoo. 4 Monotherapy with a topical steroid has proven to be acceptable for use as a short-term therapy for scalp psoriasis. 4 Topical moderate-to high-potency corticosteroids such as 0.05% clobetasol propionate, 0.25% desoximetasone, 0.1% betamethasone valerate and 0.05% betamethasone dipropionate are recommended for adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 Monotherapy with a topical steroid has proven to be acceptable for use as a short-term therapy for scalp psoriasis. 4 Topical moderate-to high-potency corticosteroids such as 0.05% clobetasol propionate, 0.25% desoximetasone, 0.1% betamethasone valerate and 0.05% betamethasone dipropionate are recommended for adult patients. 2 Cutaneous side effects of topical steroids on the scalp are rare.…”
Section: Introductionmentioning
confidence: 99%